2018
DOI: 10.1111/jbi.13204
|View full text |Cite
|
Sign up to set email alerts
|

Dated phylogeography of western North American subalpine marshmarigolds (Caltha spp., Ranunculaceae): Miocene–Pliocene divergence of hexaploids, multiple origins of allododecaploids during the Pleistocene, and repeated recolonization of Last Glacial Maximum glaciated regions

Abstract: Aim In order to understand how a montane polyploid species complex responded to Cenozoic mountain uplift and climate change, we reconstructed the biogeographic history of the subalpine marshmarigold polyploid complex, including Caltha biflora, Caltha chionophila and Caltha leptosepala. Phylogenies at multiple taxonomic levels were used to estimate the timing of species divergence, allopolyploid formation and migration patterns, and to identify Last Glacial Maximum (LGM) refugia and recolonization routes. Locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Analysis 2 suggests a crown‐group age of 76.9 Ma (95% HPD: 45.98–109.3; node 1) for the family, which is older than the estimate of Wefferling and Hoot (; 44.88 Ma), but our credibility interval overlapped with the assumptions of Anderson et al () of 66 and 95 Ma inferred by penalized likelihood and nonparametric rate smoothing methods, respectively. Wefferling and Hoot () estimated the split time between Lardizabaleae and Akebieae and the crown age of Akebieae at 18.63 and 7.86 Ma, respectively, which are in agreement with our results: 24.4 Ma (95% HPD: 12.23–41.31; node 2) and 7.49 Ma (95% HPD: 3.76–13.77; node 3). There was no temporal conflict between the South American lineage and the Tertiary wood record from Patagonia (Schönfeld, ), although the exact age of the fossil remains unclear.…”
Section: Discussionmentioning
confidence: 51%
“…Analysis 2 suggests a crown‐group age of 76.9 Ma (95% HPD: 45.98–109.3; node 1) for the family, which is older than the estimate of Wefferling and Hoot (; 44.88 Ma), but our credibility interval overlapped with the assumptions of Anderson et al () of 66 and 95 Ma inferred by penalized likelihood and nonparametric rate smoothing methods, respectively. Wefferling and Hoot () estimated the split time between Lardizabaleae and Akebieae and the crown age of Akebieae at 18.63 and 7.86 Ma, respectively, which are in agreement with our results: 24.4 Ma (95% HPD: 12.23–41.31; node 2) and 7.49 Ma (95% HPD: 3.76–13.77; node 3). There was no temporal conflict between the South American lineage and the Tertiary wood record from Patagonia (Schönfeld, ), although the exact age of the fossil remains unclear.…”
Section: Discussionmentioning
confidence: 51%
“…We set a 101 Ma maximum age for the root, which is the estimated crown age of the Chasmantheroideae (Wang & al., 2012), with a normal distribution and a standard deviation of three. A recent study reported a relatively younger age (80.14 Ma) for the crown age of the subfamily (Wefferling & Hoot, 2018). To explore the impact of the root age on the estimates, we also constrained the root to 80.14 Ma and reran the dating analysis using the cpDNA data.…”
Section: Molecular Dating Analysismentioning
confidence: 99%
“…The evolution of species is driven by the environment. To explore the key issues of evolutionary history, such as the region of origin, divergence time, radiation path, and distribution range, it is necessary to combine fossil 21 , phytogeographical 22 , ecological 23 , 24 , and other evidence to obtain reasonable and accurate results. In these aspects, there is a paucity of research on Chrysanthemum , Ajania , and their allies (but see Li et al 25 ), especially on the phytogeography and ecology within their areas.…”
Section: Introductionmentioning
confidence: 99%